Fabrication and characterization of ZnS/ZnO core shell nanostructures on silver wires - Chyuan Haur Kao (AIP Advances, 2018)
In this research, ZnS nanoparticles were synthesized on ZnO/silver wires to form ZnS/ZnO core shell structures. Various outward appearance and colors could be observed by different ZnO growth and sulfurization conditions. To evaluate the properties of these nanostructures, optical properties and chemical bindings were analyzed by photoluminescence, Raman analysis, and X-ray photoelectron spectroscopy. Furthermore, material characterizations including transmission electron microscopy and X-ray diffraction confirmed that cubic ZnS (311)/ZnO nanostructures were grown on silver wires for the first time. ZnS/ZnO core shell structures on silver wires are promising for future optoelectronic and biomedical applications.